Pengaruh Model Pembelajaran Inkuiri terhadap Kemampuan Berpikir Kritis Siswa: Literature Review - Natasya Maharani; Desy Komala Sari; Cahaya Indah; Nur Izzatil Arasyi Tyas Nurbudi; Jodion Siburian; Lely Mardiyanti; Ali Sadikin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking is an essential 21st-century skill in science and biology education. However, students’ critical thinking skills are often still relatively low due to learning processes that are less focused on investigation and active problem-solving. Inquiry learning has been widely implemented as an approach that encourages students to ac-tively construct knowledge and develop higher-order thinking skills. This study aimed to analyze the effect of the inquiry learning model on students’ critical thinking skills through a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines. Articles were collected from Google Scholar using the Publish or Perish application, covering publications from 2022 to 2026. A total of 20 articles that met the inclusion cri-teria were analyzed descriptively. The results showed that the inquiry learning model had a positive impact on students’ critical thinking skills at elementary, junior high, and senior high school levels. The most widely used form was guided inquiry, which effec-tively improved critical thinking through observation, investigation, experimentation, data analysis, and conclusion drawing. In addition, the model enhanced science process skills, collaboration, and student engagement in learning.